Monitoring the Knysna forest : species, community and forest responses - Morris, Thomas (Department of Biological Sciences, 2017)
Forests are valuable ecosystems to society but are greatly threatened by changing factors from habitat conversion to climate change. South Africa's only extent of indigenous forest is predicted to disappear within the next 30 years. Many challenges are currently faced when trying to detect and interpret directional changes in forests which results in an urgent need to understand any effects that these change factors have on forest ecosystems. We investigate evidence for change in the old growth Lilyvlei Nature Reserve by monitoring growth and dynamics at various levels by examining a 20 year record of tree growth and stand dynamics. Through the inclusion of biodiversity measures and ecologically important plant traits, changes in forest dynamics and growth are investigated. Results show no total change in biomass across the 20 year period, although an intensification of extreme climatic events and dynamics indices were recorded for the second period. Significant correlations were found between community diversity measures and forest growth. Trait variables showed insignificant correlations with forest growth and dynamics. These results suggest that the Knysna forest is controlled by climatic variables and that increased diversity within communities result in increased growth. It is believed that changes in the forest may be masked by compositional shifts of just a few dominant species. These results become important, particularly in the light of changing climatic, atmospheric and environmental changes that threaten global ecosystems in the time to come. However, considering the brief 20 year period observed in a forest where the average individual has a life span of over a century, the importance of long term monitoring becomes an important component in the understanding of forest ecosystems.